Correlations between experimental myopia models and human pathologic myopia - Vutipongsatorn, Kritchai; Jonas, Jost B. (Retina, 2019)
Purpose: To analyze the hallmark features of pathologic myopia developed in animal models and compare them with those seen in patients. - Methods: A literature review was performed to identify animal models that exhibited key features of pathologic myopia, namely posterior staphyloma, myopic maculopathy, lacquer cracks, and choroidal neovascularization, either spontaneously or induced by monocular deprivation. Using imaging modalities, such as optical coherence tomography, confocal scanning laser ophthalmoscopy, fluorescein angiography, and electron microscopy, these features were compared with those found in myopic maculopathy of patients. - Results: Three types of animals were identified. The LRP2 knockout mice exhibited posterior staphylomas and chorioretinal atrophy at 21 and 60 days after birth, respectively. Retinopathy globe enlarged (rge) chicks and normal lid-sutured chicks developed lacquer cracks and chorioretinal atrophy. Lacquer cracks detected in rge chicks subsequently progressed to patchy chorioretinal atrophy, which is also commonly seen in patients with pathologic myopia. - Conclusion: The LRP2 knockout mice, retinopathy globe enlarged (rge) chicks, and normal lid-sutured chicks exhibit features typical for myopic maculopathy in patients and could serve to further elucidate the pathogenesis of myopic maculopathy.